1992
DOI: 10.1128/aac.36.12.2852
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic activity of clarithromycin and minocycline in an animal model of acute experimental toxoplasmosis

Abstract: The efficacy of clarithromycin in a murine model of acute toxoplasmosis was studied. Clarithromycin was administered alone and concurrently with minocycline, and eficacy was assessed by survival rates and sequential determination of parasite burden in blood, brains, and lungs. ILmited protection resulted from administration of each drug alone, whereas a remarkable synergistic effect followed concurrent administration.Survival of mice treated with 200 mg of clarithromycin plus 20 mg of minocycline per kg of bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

1993
1993
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…The rate of treatment-limiting adverse events related to this combination appears to be moderate. These data support the favorable results reported for the murine model (1,3). They warrant further studies to assess this combination along with other alternative regimens, such as atovaquone (5), which might benefit the patients unable to tolerate conventional therapies.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…The rate of treatment-limiting adverse events related to this combination appears to be moderate. These data support the favorable results reported for the murine model (1,3). They warrant further studies to assess this combination along with other alternative regimens, such as atovaquone (5), which might benefit the patients unable to tolerate conventional therapies.…”
supporting
confidence: 77%
“…They were six men and two women with a mean age of 28 to 38 years and a mean CD4 count of 18 Ϯ 15 cells/mm 3 . All patients had toxoplasmosis diagnosed after suggestive contrast-enhancing lesions were found at the initial CT scan (n ϭ 7), before any anti Toxoplasma gondii treatment was started, or after detection of T. gondii in broncho-alveolar lavage (patient 8).…”
mentioning
confidence: 99%
“…With the combinations of dihydrofolate reductase inhibitors and sulfonamides, strong synergistic activity has been observed both in vitro and in vivo, because of the sequential activity of the drugs on the folate metabolism of the parasite (5,8,20). With some other combinations, marked in vivo synergy can be obtained in the absence of an in vitro interaction, possibly because of the complementary effects of the compounds on different sites of Toxoplasma infection (4,6,7). In the present study, no synergistic interaction either in vivo or in vitro could be clearly demonstrated.…”
Section: Discussionmentioning
confidence: 87%
“…Combination studies were performed in two separate experiments, with atovaquone administered at 50 mg/kg/day in combination with pyrimethamine or sulfadiazine (experiment 1) and clarithromycin or minocycline (experiment 2). For each drug combination, we selected a dose that was previously found to be noncurative, i.e., clarithromycin at 50 mg/kg, sulfadiazine at 200 mg/kg, pyrimethamine at 12.5 mg/kg, and minocycline at 50 mg/kg (6,7,20). Drug suspensions were prepared daily in a solution of methyl cellulose-carboxymethyl cellulose-0.1% Tween 20, briefly sonicated, and administered orally to mice via tube feeding.…”
mentioning
confidence: 99%
“…Tetracyclines and macrolides have antimicrobial activity, alone and in combination with other drugs, against other eukaryotic organisms, including algae (10), fungi (11,14,22), and protozoa (6,12). Although the mechanism of action of these drugs on eukaryotic organisms is not completely understood, the main mechanisms described include the inhibition of protein synthesis (14,17) and selective inhibition of both mitochondrial and plastid activity (12) and intracellular calcium release (22).…”
mentioning
confidence: 99%